STRUKTUR KEPEMILIKAN, MEKANISME TATA KELOLA PERUSAHAAN, DAN BIAYA KEAGENAN DI INDONESIA (Studi Empirik pada Perusahaan di Bursa Efek Indonesia) - Hadiprajitno, Paulus Basuki (Department of Accounting, Faculty of Economics & Business,Diponegoro University, Indonesia, 2013)
This study is to examine the effect of corporate governance (the owners’s character and thegovernance mechanism) on agency cost. This research shows that family ownership, financialinstitution ownership, government ownership, and foreign ownership have negative effects onagency cost that is proxied as managerial operation cost and or as assets turnover, compared topublic ownership. Furthermore, ownership concentration of at least 5 percent each is not provento effect the agency cost. Results of other examination show that the proportion of independentboard and the number of board meetings have negative effects to the agency cost that is proxiedas assets turnover. However, these two variables and the number of audit committee meetinghave the opposite effect to the agency cost when it is proxied as managerial operation cost.Theseinconsistencies are caused by the ineffective implementation of corporate governance mechanismin Indonesia even after 10 years of implementation.